2022
DOI: 10.1186/s40249-022-01047-y
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and perceptions of COVID-19 infection and vaccination among Palestinian refugees in Jerash camp and Jordanian citizens: a comparative cross-sectional study by face-to-face interviews

Abstract: Background During the COVID-19 vaccination, the access to vaccines has been unequal among countries and individuals, for example low-income countries displayed significant low levels of vaccination. Furthermore, most refugees are living in developing low-income countries which struggling to access the essential health-care services including vaccination. Thus, the objective of this study was to assess the experiences and perceptions of COVID-19 infection and vaccination among Palestine refugees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…According to the 118 literature review and based on the conceptual framework used (10) 4). Female gender (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), younger age (14,15,17,(22)(23)(24)(25)(26)(27)(28)(29), lower level of education (12,16,17,19,20,22,26,(30)(31)(32), and being single (11,13,26) were associated with lower vaccine acceptance in most studies. Some of the other sociodemographic influencers of COVID-19 vaccine acceptance were sexual orientation (19),income (26,33), region of origin (11,17,21), religion (11,17), migratory background (20,30,34,…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…According to the 118 literature review and based on the conceptual framework used (10) 4). Female gender (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), younger age (14,15,17,(22)(23)(24)(25)(26)(27)(28)(29), lower level of education (12,16,17,19,20,22,26,(30)(31)(32), and being single (11,13,26) were associated with lower vaccine acceptance in most studies. Some of the other sociodemographic influencers of COVID-19 vaccine acceptance were sexual orientation (19),income (26,33), region of origin (11,17,21), religion (11,17), migratory background (20,30,34,…”
Section: Resultsmentioning
confidence: 92%
“…Most common sociodemographic factors associated with COVID-19 acceptance were gender, age, level of education, and marital status (Table 4). Female gender (11-21), younger age (14, 15, 17, 22-29), lower level of education (12, 16, 17, 19, 20, 22, 26, 30-32), and being single (11, 13, 26) were associated with lower vaccine acceptance in most studies.…”
Section: Methodsmentioning
confidence: 89%
“…Various studies [ 56 , 57 ] implied that population groups having experience with COVID-19 infections were more likely to accept the COVID-19 vaccination. Al-Hatamleh Mohammad A. I. et al [ 58 ] reported that many symptoms, including general fatigue, headache, fever, anosmia, and cough, were the most frequent health burdens of COVID-19 infection. Populations were willing to take the COVID-19 booster dose vaccinations for reducing the suffering of COVID-19 infections [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…[11] Equally, a low COVID-19 testing rate in these settlements was a contributing factor for a low rate of reported cases, and the refugees who were infected with COVID-19 may have gone unnoticed by this issue. [12] On the other hand, the impact of the COVID-19 pandemic on settled migrants' has intensified preexisting social inequalities in these settings, such as forced displacement, disruptions of necessary health services and reduction of social networks, thus affecting their mental health status. [13,14] In the general population, the course of the pandemic has worsened mental health levels, leading in some cases to an increase in the demand for psychological care.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] Equally, a low COVID-19 testing rate in these settlements was a contributing factor for a low rate of reported cases, and the refugees who were infected with COVID-19 may have gone unnoticed by this issue. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%